2018
DOI: 10.14419/ijet.v7i4.38.27633
|View full text |Cite
|
Sign up to set email alerts
|

Receiving and Responding to WhatsApp Official Group Messages Among Employees: An Early Interpretation Analysis

Abstract: The purpose of this article is to provide an initial analysis of the study related to the process of receiving and responding to the WhatsApp official group messages at work. Many previous studies have focused on the usage factors, advantages and disadvantages, as well as the implications of using WhatsApp. But this paper will reveal the interpretation of a small group of employees at Universiti Utara Malaysia of their roles and actions related to WhatsApp official group messages. A total number of five admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, the current development of WhatsApp has presented a new service called WhatsApp Business that supports sales using WhatsApp. One of the features that has the most impact is sending messages in bulk, but there are still obstacles, namely only recipients who have added the sender's WhatsApp contact can receive the message [10]. Therefore, a program is needed that can replace the activities carried out by business actors for sending messages on WhatsApp so that promotions can be carried out more easily.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current development of WhatsApp has presented a new service called WhatsApp Business that supports sales using WhatsApp. One of the features that has the most impact is sending messages in bulk, but there are still obstacles, namely only recipients who have added the sender's WhatsApp contact can receive the message [10]. Therefore, a program is needed that can replace the activities carried out by business actors for sending messages on WhatsApp so that promotions can be carried out more easily.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Statista reported that Malaysia is the second-highest country for WhatsApp market penetration after Saudi Arabia (Statista, 2018). In Malaysia, this mobile application technology was used as a communication and collaboration platform in organizations (Attalla et al , 2020; Omar et al , 2018; Ganasegeran et al , 2017) .…”
Section: Introductionmentioning
confidence: 99%